2008
DOI: 10.1590/s1415-47572008000200021
|View full text |Cite
|
Sign up to set email alerts
|

First report of a B chromosome in a natural population of Astyanax altiparanae (Characiformes, Characidae)

Abstract: Several species of the genus Astyanax have already been genetically studied, and B-chromosomes have been considered to be an interesting feature in some species of this group. In the present paper we report, for the first time, the occurrence of a B microchromosome in a natural population of A. altiparanae. This additional genomic element was identified as an acrocentric chromosome, similar in size to the smallest chromosomal pairs of the standard karyotype. Analysis of the constitutive heterochromatin pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…The analysis of constitutive heterochromatin patterns showed heterochromatic blocks in the pericentromeric regions of most chromosomes and evident signals in the terminal regions of some chromosomes (Figure 2), similar to those found in other populations of A. bockmanni (Kavalco et al 2009;Hashimoto and Porto-Foresti 2010). In relation to the B chromosomes, all three morphological variants (B M , B m , and B a ) were identified as heterochromatic (Figure 2), in accordance with a common characteristic reported for B chromosomes in the genus Astyanax (Néo et al 2000;Moreira-Filho et al 2001;Hashimoto et al 2008;Machado et al 2012).…”
Section: Resultssupporting
confidence: 87%
“…The analysis of constitutive heterochromatin patterns showed heterochromatic blocks in the pericentromeric regions of most chromosomes and evident signals in the terminal regions of some chromosomes (Figure 2), similar to those found in other populations of A. bockmanni (Kavalco et al 2009;Hashimoto and Porto-Foresti 2010). In relation to the B chromosomes, all three morphological variants (B M , B m , and B a ) were identified as heterochromatic (Figure 2), in accordance with a common characteristic reported for B chromosomes in the genus Astyanax (Néo et al 2000;Moreira-Filho et al 2001;Hashimoto et al 2008;Machado et al 2012).…”
Section: Resultssupporting
confidence: 87%
“…However, Voltolin et al (2011) recently detected the presence of eight and nine supernumerary chromosomes in individuals of this species resulting from induced crossings. Supernumerary chromosomes exhibit a remarkable variation in size and morphology among fish, i.e., the occurrence of large genomic elements as macrochromosomes was described in species of the genus Astyanax (Maistro et al 1992, Salvador and Moreira-Filho 1992, Vicente et al 1996, Moreira-Filho et al 2001, Ferro et al 2003, Hashimoto et al 2008; of medium size in Rhamdia Bertollo 1990, Fenocchio et al 2000); and also as small elements identified as microchromosomes in Prochilodus (Pauls and Bertollo 1983, Venere et al 1999, Cavallaro et al 2000, Oliveira et al 2003, Voltolin et al 2009). Artoni et al (2006), studying specimens of P. lineatus from the Mogi-Guaçu River, observed the presence of three types of supernumerary microchromosomes in this species, which were classified as B-acrocentric, B-metacentric, and B-submetacentric.…”
Section: -1377mentioning
confidence: 99%
“…Therefore, little is known about the karyotype structure of this group, and the literature is practically limited to the genus Astyanax (Baird and Girard, 1854), for which a wide numeric and morphologic variability is very evident (Pazza et al, 2006;Hashimoto et al, 2008;Kantek et al, 2008;among others).…”
Section: Introductionmentioning
confidence: 99%